Synthesis of Polyvinyl Alcohol (PVA)-Gelatin Hydrogel from White Snapper (Lates calcarifer, Bloch) with Gamma Irradiation and Its Characterizations - H Hariyanti; E Erizal; R. Z. Apriyani; D. P. Perkasa; I. Lestari; H. Rahmi (National Research and Innovation Agency, 2023)
The application of nuclear technology in the health sector is increasing. One example is the use of irradiation in production of wound dressings. Research activities have been conducted to study whether polyvinyl alcohol (PVA)-gelatin-based hydrogel from white snapper scales can be processed using gamma irradiation into wound dressings. A series of PVA (10 %) solutions containing gelatin in various concentrations (0-4 %) were treated with three freeze-thaw cycles and then irradiated at doses of 10 and 20 kGy. They were subsequently characterized using Fourier transform infrared (FTIR) spectroscopy and scanning electron microscope (SEM). Gel fraction, water absorption, and percentage of hydrogel water evaporation rate were tested gravimetrically, while the elongation at break and the tensile strength of the hydrogels were tested with a universal testing meter. The evaluation showed that the hydrogel gel fraction decreased with increasing gelatin concentration from 0 % to 4 % for both irradiation doses (10 and 20 kGy). The rising gelatin concentration demonstrated that increasing gamma radiation dose improved the hydrogel's water absorption, evaporation rate, tensile strength, and elongation at break. PVA-gelatin hydrogel with irregular pore structure was observed from SEM test results. The FTIR measurement results confirmed the formation of crosslinks in the hydrogel matrix. The PVA-gelatin hydrogel produced through gamma irradiation could be used for wound dressings.